Increased mast cell abundance in adipose tissue of metabolic syndrome: relevance to the proinflammatory state and increased adipose tissue fibrosis - Gurung, Purnima; Moussa, Karine; Adams-Huet, Beverley; Devaraj, Sridevi; Jialal, Ishwarlal (American journal of physiology: endocrinology and metabolism, 2019)
Metabolic Syndrome (MetS) affects 35% of American adults > 40 yr and portends an increased risk for both atherosclerotic cardiovascular disease (ASCVD) and diabetes. The role of mast cells in the proinflammatory state of MetS is not well elucidated. We propose that mast cells in subcutaneous adipose tissue (SAT) of MetS patients without diabetes or clinical ASCVD contribute to insulin resistance and inflammation. Matched controls ( n = 15) and MetS ( n = 19) subjects were recruited from Sacramento, CA, and selected based on Adult Treatment Panel III criteria. SAT biopsy was performed on all subjects and processed for immunohistochemistry. The SAT sections were stained using Astra Blue stain and tryptase stain for mast cells. Fasting blood was obtained for chemistries and biomarkers. Abundance of mast cells (Astra Blue stain) in SAT of MetS subjects compared with controls was increased 2.5-fold ( P < 0.0001). Mast cells correlated positively and significantly with waist circumference, glucose, triglycerides, homeostatic model of assessment-insulin resistance (HOMA-IR), AT insulin resistance, leptin, interleukin (IL)-1β, IL-6, chemerin, p38 MAPK activity, and nuclear factor κB activity in circulating monocytes. Mast cells also correlated significantly with markers of fibrosis and angiogenesis. Tryptase staining of mast cells in AT revealed a significant increase ( P = 0.008) with similar correlations. We make the novel observation that there are increased mast cells in SAT of MetS, and these mast cells correlate with insulin resistance (hepatic and adipose tissue), inflammation, and AT fibrosis. Hence, these immune cells appear to occupy a pivotal role in the pathogenesis of MetS.